Effect of Preoperative Respiratory Rehabilitation in Patients Undergoing Cardiac Surgery - Sonja Nejkov; Vesna Bokan-Mirković; Nataša Đukić-Macut; Marina Vuković (Acta Clinica Croatica, 2020)
The aim of the study was to evaluate the effects of preoperative respiratory rehabilitation on functional capacity, length of stay in intensive care unit (ICU), duration of mechanical ventilation (MV) and total hospitalization, as well as to estimate arterial blood gas (ABG) values in patients undergoing cardiac surgery. Nineteen patients were included in the randomized observational study, divided into two groups: group A (intervention) and B (control). Preoperative and postoperative rehabilitation was performed in group A, and only postoperative rehabilitation in group B. Rehabilitation was carried out according to a predefined protocol. We used ABG to evaluate respiratory function, two-minute walk test (2MWT) and sit-to-stand test to assess functional capacity. The following data were obtained from medical documentation: duration of MV, length of stay at ICU, occurrence of postoperative pulmonary complications, and length of total hospitalization in both groups. Significant between-group difference was found for the length of total hospitalization and duration of MV (p<0.05 both). Analysis of the mean values of 2MWT on the last day of hospitalization (p=0.005), sit-to-stand test before surgery (p=0.022) and on the last day of hospitalization (p=0.008) showed statistically significant differences. The length of hospital stay significantly correlated with preoperative rehabilitation in group A (r=0.885; p<0.0001). There was no difference in ABG parameters between the groups. The study showed that preoperative respiratory rehabilitation had an effect on reducing duration of MV and length of total hospitalization, and improved functional capacity.